Inggris Understanding the Characteristics of Human Milk Sharing in Daerah Istimewa Yogyakarta: A Descriptive Quantitative Study - Rachmawati Widyaningrum; Elievia Wienarno; Zly Wahyuni; Hesti Khofifah; Yuni Herliyanti (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2021)
Human milk donors (HMD) is one of the alternatives foods for the baby if the mother's breastmilk production is insufficient. However, unpasteurized and peer donor milk sharing is not recommended way due to safety concerns. On the other hand, the rate of HMD in Indonesia increased significantly and might be followed by its disease transmission risk by informal milk sharing. This cross-sectional study aimed to figure the HMD characteristics in Daerah Istimewa Yogyakarta (DIY), including the mother's knowledge and practices, the proportion of mothers who give and receive HMD, the reason, and their breastfeeding status. Among 153 participants, 9.1 % only received donor milk, 19.6% of them donated their breast milk (BM), and 5.2% did both receiving and donating BM. However, 43.1% of them have a lack of knowledge, and only 13.1% knows that they should not ask for HMD through informal way. Most of the mothers seek HMD because of the feeling of insufficient BM production. Concerning the rate of mothers who donated or received HMD, their level of knowledge, and the number of inappropriate human milk sharing, we underline the importance of breastfeeding support, education, and regulation of HMD to minimize the health risk of inappropriate human milk sharing.